Early construction cost and time risk assessment and evaluation of large-scale underground cavern construction projects in Singapore - Maruvanchery, Varun (2021)
The applicability of the Decision Aids for Tunneling (DAT) as an early construction cost and time predicting tool for large-scale underground cavern construction projects is investigated in this study. For this purpose, three large-scale underground cavern construction projects in Singapore are presented using the proposed framework. The data from Project A, which is already completed, are used to validate the prediction outcomes. The results show that the proposed workflow can well estimate the construction cost and time at the 95% confidence level. The DAT simulation results of the other two projects, which are in the early planning stages, are compared with Project A to assess the accuracy of the predicted cost and time. The results show that the proposed workflow with the DAT as a predictor is a valuable tool in estimating construction cost and time for large-scale underground cavern projects, particularly for feasibility studies.